PENGARUH BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN (STUDI KASUS PADA PERAWAT RUMAH JIWA TAMPAN PEKANBARU) - Alvin Fitrihady; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to determine the effect of organizational culture and work environment on employee performance partially and simultaneously. This study uses a questionnaire as a data collection tool that is distributed to 61 respondents at the Tampan Mental Hospital Pekanbaru. The data is then processed using descriptive analysis and statistical analysis using SPSS 23 by conducting validity, reliability testing, simple linear regression analysis, multiple linear regression analysis, determination analysis (R2) and hypothesis testing by t test (partial) and F test (simultaneous).The results showed that the first hypothesis testing is organizational culture on employee performance, namely t arithmetic (3.883)> t table (2.001), meaning that organizational culture has a significant effect on employee performance. Second, the work environment is t arithmetic (4,723)> t table (2,001), meaning that the work environment has a significant effect on employee performance. F test results (14.926)> F table (3.16) means that the organizational culture and work environment simultaneously have a significant effect on employee performance. Keywords: Organizational Culture, Work Environment, Employee Performance